A Review on Insomnia: The Sleep Disorder - Atika Pusparani (Scientia Psychiatrica, 2021)
Insomnia is the inability to fall or stay asleep, even when one has the opportunity to do so. People who suffer from insomnia may be unsatisfied with their sleep and exhibit one or more of the following symptoms: weariness, low energy, problems concentrating, mood swings, and poor work performance. Insomnia can be classified based on how long it lasts. Acute insomnia is a type of insomnia that lasts only a few hours and is caused by a variety of factors. Many people have had this form of temporary sleep disruption, which usually goes away without medication. Chronic insomnia is defined as sleep disruption that lasts at least three months and occurs at least three evenings per week. Insomnia can be caused by a variety of factors. Insomnia is caused by a misalignment of sleep-inducing neurotransmitters. The Insomnia Severity Index and the Pittsburgh Sleep Quality Index are two methodologies and indices that have been used to research sleep disturbances in insomnia sufferers. Many medicines, such as antidepressants and benzodiazepines, are used in the treatment, and drinking Melatonin-rich milk has also been found to be useful.